Civil, Materials and Computing Engineering - Sung, Wen-Pei; Kao, Jimmy C. M. (Jimmy Chih-Ming) 1963- (Advanced materials research, 2014)
Collection of selected, peer reviewed papers from the 2014 International Conference on Civil, Materials and Computing Engineering (ICCMC 2014), December 6-7, 2014, Taiwan. The 277 papers are grouped as follows: Chapter 1: Materials Engineering and Technologies, Chapter 2: Applied Mechanics, Geo Science, Building, Structural and Civil Engineering, Chapter 3: Power, Energy and Thermal Research, Environmental Engineering, Chapter 4: Mathematical Analysis, Computer Science, Communication and Information Technologies, Chapter 5: Mechanical Engineering, Measurement, Control and Automatisation, Chapter 6: Engineering Management, Business and Economics